Copy Number Variation of UGT 2B Genes in Indian Families Using Whole Genome Scans - Avinash M. Veerappa; Prakash Padakannaya; Nallur B. Ramachandra (Journal of Nucleic Acids)
Background and Objectives. Uridine diphospho-glucuronosyltransferase 2B (UGT2B) is a family of genes involved in metabolizing steroid hormones and several other xenobiotics. These UGT2B genes are highly polymorphic in nature and have distinct polymorphisms associated with specific regions around the globe. Copy number variations (CNVs) status of UGT2B17 in Indian population is not known and their disease associations have been inconclusive. It was therefore of interest to investigate the CNV profile of UGT2B genes. Methods. We investigated the presence of CNVs in UGT2B genes in 31 members from eight Indian families using Affymetrix Genome-Wide Human SNP Array 6.0 chip. Results. Our data revealed >50% of the study members carried CNVs in UGT2B genes, of which 76% showed deletion polymorphism. CNVs were observed more in UGT2B17 (76.4%) than in UGT2B15 (17.6%). Molecular network and pathway analysis found enrichment related to steroid metabolic process, carboxylesterase activity, and sequence specific DNA binding. Interpretation and Conclusion. We report the presence of UGT2B gene deletion and duplication polymorphisms in Indian families. Network analysis indicates the substitutive role of other possible genes in the UGT activity. The CNVs of UGT2B genes are very common in individuals indicating that the effect is neutral in causing any suspected diseases.